Aumento de la inequidad de los ingresos y de la pobreza : durante la liberalización económica y la crisis - VOS , ROB (2001)
Application of a methodology of “microsimulations” to two episodes in recent Ecuadorian economic history suggest that the observed rise in income inequality scems to be closely associated with the effects of trade liberalisation, which has led to greater demand for skilled workers and pushed unskilled workers. into unemployment or (informal) sel f-employed activities. This appears to have becn counteracted somewhat by rising participation rates, falling unemployment and real wage increases during the period of stabilisation and growth (1990-95), facilitated by greater capital inflows. The macroeconomic downturn in the second half of the 1990s made these factors compound the rise in mequality, as much as explain the steep rise in poverty.